THE INFLUENCE OF TASK COMPLEXITY AND WORKLOAD ON JOB SATISFACTION AMONG CONTRACT ELEMENTARY SCHOOL TEACHERS IN THE KEMRANJEN SUB-DISTRICT - Yustie, Herawati Anggraeni; Sunarso, Ali (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
This research examines and analyzes the influence of task complexity and workload on the job satisfaction of non-permanent (contract) elementary school teachers, both partially and simultaneously. The research was conducted on all non-permanent teachers serving in the Kemranjen Sub-district, Banyumas Regency. A quantitative research approach was employed using multiple linear regression analysis. The sampling technique employed was saturated sampling, resulting in a sample of 32 respondents that represented the entire population. Data were collected through questionnaires distributed directly to the respondents. The analysis revealed that task complexity has a negative and significant effect on the job satisfaction of non-permanent teachers, as indicated by a significance value of less than 0.05 and a t-count of -4.245. Conversely, the workload variable did not significantly impact job satisfaction, indicated by a significance value greater than 0.05 and a t-count of 0.987. However, when task complexity and workload were analyzed simultaneously, both variables significantly influenced the job satisfaction of non-permanent elementary school teachers in the Kemranjen Sub-district, contributing 43.1% to the variance explained. These findings suggest that compared to workload, task complexity plays a more significant role in enhancing the job satisfaction of contract teachers. Therefore, the results of this research may serve as a reference for policymakers in designing strategies to improve the well-being and work effectiveness of non-permanent teachers at the elementary school level. These welfare improvement efforts are expected to create a more supportive and productive work environment for non-permanent teachers.